UNINTENTIONAL CHILDHOOD POISONING, EPIDEMIOLOGY AND STRATEGIES FOR THE PREVENTION AND POLICY CHANGE IN PAKISTAN - Hassan, Omer ul; Qadri, Hasana; Mir, Umer; Ahmed, Bilal (Journal of Ayub Medical College Abbottabad, 2013)
Poisoning is the fifth leading cause of unintentional injuries among young children. Agents most commonly ingested by young children include medicines, cleaning substances, hydrocarbons, pesticides and cosmetics. Children with less educated fathers, living in more crowded conditions and from lower income families are more predisposed to unintentional poisoning. Unsafe storage of medicines, chemicals and other hazardous substances is one of the leading reasons for childhood poisoning. Knowledge of parents and caregivers about prevention of poisoning may be the basis to prevent subsequent injuries. This paper is a review of the epidemiology of unintentional poisonings among young children (less than five years) and its risk factors especially in the context ofPakistan. Keywords: Unintentional Poisoning, Review, Prevention, Pakistan